Sertoli Cell Tumors of the Testes: Systematic Literature Review and Meta‐Analysis of Outcomes in 435 Patients. (11th February 2020) - Grogg, Josias; Schneider, Kym; Bode, Peter Karl; Kranzbühler, Benedikt; Eberli, Daniel; Sulser, Tullio; Lorch, Anja; Beyer, Joerg; Hermanns, Thomas; Fankhauser, Christian Daniel
Abstract: Background: Sertoli cell tumors (SCTs) of the testes are rare, and the literature provides only weak evidence concerning their clinical course and management. The objective of this study was to summarize evidence on SCTs' clinical presentation, clinicopathological risk factors for malignancy, treatment options, and oncological outcomes. Materials and Methods: Data sources included Medline, Embase, Scopus, the Cochrane Database of Systematic Reviews, and Web of Science. Published case reports, case series, and cohorts were included. Data on clinicopathological variables, treatment of local or metastatic disease, site of metastasis, or survival were extracted from each study considered in this paper, and associations between clinicopathological variables and metastatic disease were analyzed. Whenever feasible, data on individual patients were collected. Results: Of the 435 patients included, only one (<1%) showed local recurrence after testis‐sparing surgery (TSS). Three patients underwent adjuvant retroperitoneal lymphadenectomy. Fifty patients presented with metastases, located in the retroperitoneal lymph nodes (76%), lungs (36%), and bones (16%); median time to recurrence was 12 months. Risk factors for metastatic disease included age, tumor size, necrosis, tumor extension to the spermatic cord, angiolymphatic invasion, and mitotic index. Patients with metastases had a median life expectancy of 20 months. In six patients, metastasectomy resulted in complete remission. Conclusion: Our findings suggest that few local recurrences result after TSS, and no adjuvant therapy can be regarded as a standard of care. Several risk factors are predictive of metastatic disease. Surgery leads to remission in metastatic disease, whereas systemic treatment alone does not result in long‐term remission. Implications for Practice: Testicular Sertoli cell tumors usually present without metastatic disease and show low local recurrence rates after testis‐sparing surgery; no adjuvant therapy option can be regarded as a standard of care. Patients with risk factors should undergo staging investigations. Those with metastatic disease have poor prognoses, and metastasectomy may be offered in selected cases. Abstract : Considering the rarity of Sertoli cell tumors, there are unanswered questions about optimal treatment for patients with localized or metastatic disease. This review of the literature presents the available information on clinical presentation, treatment options, and patient outcomes, as well as clinicopathological risk factors associated with metastatic disease.